The phytohormone jasmonic acid is involved in rice resistance to Southern rice black-streaked dwarf virus - Chaorui Huang; Qing Liu; Qingling Qi; Chenfei Gao; Lulu Li; Yanjun Li; Jianping Chen; Zongtao Sun; Jianlong Xu; Hehong Zhang (Crop Journal)
Viruses are significant pathogens causing severe plant infections and crop losses globally. The resistance mechanisms of rice to viral diseases, particularly Southern rice black-streaked dwarf virus (SRBSDV), remain poorly understood. In this study, we assessed SRBSDV susceptibility in 20 Xian/indica (XI) and 20 Geng/japonica (GJ) rice varieties. XI-1B accessions in the Xian subgroup displayed higher resistance than GJ accessions. Comparative transcriptome analysis revealed changes in processes like oxido-reductase activity, jasmonic acid (JA) metabolism, and stress response. JA sensitivity assays further linked antiviral defense to the JA pathway. These findings highlight a JA-mediated resistance mechanism in rice and offer insights for breeding SRBSDV-resistant varieties.